Influence of Data Mining Techniques in Healthcare Research - P.Chandrakala,Dr.A.Sumithra,Dr.A.Saranya, .Dr.R.Bagavathi Lakshmi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Healthcare research is essential to modern society because increasing of new diseases makes the people despondent. In the 21st century, all the hospital becomes computerized and keeps all the medical records and transactions in the repository. One of the core research domains like image processing give significant advancement in healthcare and even data mining also contributed as well. Data mining is the research area that extracts knowledge from the data repository. The mining algorithms like clustering and classification can be applied in many areas like brain tumor detection, cancer detection, heart dieses, hospital management, cell mutation, etc. This study paper explores such algorithms, architectures, and problems that are developed by various researchers. This paper focus on the results belongs to a brain tumor and advanced mining techniques on medical records.